Antigenic alteration of 2017-2018 season influenza B vaccine by egg-culture adaption - Wilson, Jo L.; Zhou, Ruifeng; Liu, Hsuan; Rothman, Richard; Fenstermacher, Katherine Z.; Pekosz, Andrew (Frontiers in Virology, 2022)
Influenza B Viruses (IBV) have caused an increasing number of cases over the last 15 years. The focus of this study was to assess the role of egg adapted mutants in IBV vaccines on the reactivity of serum from vaccinated or IBV infected individuals. We focused on the 2017-2018 IBV as this was a significant influenza year with reported low vaccine effectiveness by the CDC. Patient samples were obtained from Johns Hopkins Adult Emergency Room for virus isolation and antigenic characterization. Antigenic characterization was evaluated using neutralizing antibody assays. Viral characterization was carried out using viral genome sequencing and structural modeling, MDCK-SIAT growth curves, MDCK Plaque assays and human primary nasal epithelial cell (hNEC) growth curves. In our analysis, we found that in the vaccine strains of both IBV lineages , there was a mutation at position 197 (B/Brisbane HA Numbering) that leads to a loss of glycosylation Our antigenic evaluation shows that there is a significant difference in neutralizing antibody titers between the egg adapted vaccine for the B/Yamagata lineage compared to representative clinical isolates from that season and the cell cultured vaccine. We propose that this loss of a glycosylation site is an important site for propagation in the allantois and that this common site change may play a role in antigenic recognition and therefore immune protection from circulating viruses. Screening egg cultured vaccine viruses for egg adapted mutants, further transitioning vaccine production to mammalian culture models (MDCK) or investigating new models of influenza vaccination may be necessary to improve efficacy of the seasonal influenza vaccine for protection from IBV.